Response to COVID-19 : Preparing for School Re-Opening – The Case of South Korea - World Bank (World Bank, Washington, DC, 2020)
In this note the reader will learn : The new school year began with online classes for the first time. How the Ministry Of Education (MOE) and local education offices secured digital devices to lend to students in need, and schools prepared online class guidelines, including the class hours, format, attendance, and evaluation. How the government mobilized academia, government-led institutions, and the private sector to overcome technical problems, increased burden of teachers, and equity issues in learning from online classes. In preparing for the physically reopening of schools, it is important to prepare strategies to respond to any additional extended breaks if the virus comes back and to enable local authorities and schools to develop their reopening plans to prioritize the needs of students and the local community, and implement it working with the community partners. Using this crisis to build an education system that can reach everyone and be resilient and sustainable in a time of crisis.